EFFECTIVE BRANDING STRATEGY TO BUILD A STRONG BRAND - Hendra Permana (Jurnal Scientia, 2023)
This research aims to investigate and analyze effective branding strategies in forming a strong brand. Branding is a crucial aspect in differentiating products or services from competitors in an increasingly competitive market. A strong brand has the ability to attract consumer attention, maintain loyalty, and create long-term value for the company. This research uses a qualitative approach with descriptive methods. The research results show that building a strong brand for large companies requires an effective branding strategy. This includes steps such as creating an attractive logo, using efficient marketing strategies, inserting value in the product, conducting market and competitor research, finding a unique position, carrying out appropriate promotions, and collaborating with external parties. It is also important to maintain brand consistency and face challenges such as fierce competition, changing market trends and economic uncertainty. Although complex, overcoming these challenges is key to building a strong, relevant and sustainable brand, which will help companies remain successful in an ever-changing marketplace.